Analisis Kuantitatif Pengaruh Getaran Mesin Terhadap Umur Fatik Struktur Rangka Dump Truck Kapasitas Besar Pada Kondisi Pembebanan Dinamis - Frederik Demmatacco; Nevada Nanulaitta; Graciadiana I Huka (Journal Mechanical Engineering, 2026)
Large-capacity dump truck operations in mining environments generate cyclic dynamic loads originating from engine vibration, uneven haul road surfaces, and inertial forces from acceleration and braking, which potentially trigger fatigue damage accumulation in the vehicle chassis frame structure. This study aims to characterize the engine vibration spectral profile, map the dynamic stress distribution at critical frame zones, and quantitatively assess the contribution of engine vibration to fatigue life prediction in an integrated manner. The methodology integrates three primary approaches, namely in-situ vibration measurement based on Power Spectral Density analysis, frequency-domain Finite Element Analysis simulation, and fatigue life prediction utilizing rainflow counting combined with Miner's Rule. Measurement results reveal a peak Power Spectral Density value of 0.0842 g²/Hz under full-load conditions at 2,100 RPM. Numerical simulation confirms a maximum von Mises stress of 487 MPa at the front cross member welded joint, exceeding the material fatigue limit of 310 MPa. Fatigue life prediction at the most critical point reaches approximately 11,494 operational hours, with engine vibration contributing 38.6% of the total accumulated damage. These findings establish engine vibration as the second largest determinant of chassis structural degradation, making engine mounting system optimization and remaining fatigue life-based predictive maintenance the primary recommendations of this research. Keywords: engine vibration; fatigue life; finite element analysis; Miner's Rule; mining dump truck